CleanMyCoastal: Coastal Clean-up Volunteering Application - Ooi, Nicholas Zhee Chen (2023)
Beach litter has become a concerning issue to society as it brings adverse effects on humans, aquatic life, and the environment. To overcome the beach litter issues, our local beach conservation NGOs have consistently launched beach clean-up events to reduce the beach litter issues in Malaysia. Nevertheless, these NGOs faced challenges in holding their beach cleanings, such as recruitment and retention of volunteers, financial support, and event management. Moreover, the process of joining a beach cleaning event is inefficient due to there is no unified volunteering platform and volunteering management platform available in Malaysia. Therefore, the CleanMyCoastal application is proposed in this project to overcome the issues faced by marine conservation NGOs and volunteers. CleanMyCoastal is developed to help NGOs manage their beach cleaning event, such as recruiting and retaining volunteers. On the other hand, the system's users can send alerts on the coastal pollution found around the Malaysian coast. With the alerts created, the NGO will be able to stay alert and create events based on the alert location. NGOs can also efficiently manage their volunteers by assigning tasks to their volunteers. CleanMyCoastal also provides sharing stories and chat features to keep the NGOs engaged with the beach cleaning community. CleanMyCoastal has successfully deployed through the Rapid Application Development method.